Pembelajaran Bahasa Arab Di Lembaga Bahasa Masjid Agung Sunan Ampel Surabaya (LPBA-MASA) - Arum Kusmila Surya Putri; Dita Wahyuni Aristantia; Qomariyah Qomariyah; Putri Amalia; Mamluatur Rohmah (Departement of Mathematics Education, 2023)
One of the non-formal institutions that is looking for practical ways to learn Arabic is the Arabic Language Learning Institute at the Great Mosque of Sunan Ampel (LPBA-MASA). This institution, inherited from Sunan Ampel, has a great responsibility to carry forward the mission of spreading Islam. Bringing majesty through language learning and development, the Arabs are specifically aimed at the younger generation and the people in general. The Institute of Lectures and Arabic Courses of the Great Mosque of Sunan Ampel LPBA-MASA is one of the efforts to fill the activities of the Sunan Ampel Grand Mosque Surabaya. A mosque that originally featured islamic boarding school and educational style buildings around it. This institution is located on Jl. Ampel Masjid 53 Surabaya (Sunan Ampel Grand Mosque Complex). The author would like to investigate the Arabic learning systems used in various LPBA-MASA methods to explore their impact and results on students. The method used in the LBPA-MASA and LPBA-MASA infrastructure focuses on the problems of the Arabic learning system in LBPA-MASA